NEAT1 mediates paclitaxel-resistance of non-small cell of lung cancer through activation of Akt/mTOR signalling pathway. (26th November 2019) - Li, Baiying; Gu, Wenyue; Zhu, Xinhai
Abstract: Development of paclitaxel-resistance is a main problem during non-small cell lung cancer (NSCLC) chemotherapy. Nuclear paraspeckle assembly transcript 1 (NEAT1) is an oncogenic long non-coding RNA (lncRNA) which has been proved to be aberrantly upregulated in many human malignancies. In this study, we investigated the mechanism by which NEAT1 contributed to paclitaxel-resistance in NSCLC. NEAT1 was upregulated significantly in paclitaxel-resistant NSCLC cell line, compared with other NSCLC cell lines and normal bronchial epithelial (BE) cell line. Knockdown of NEAT1 could reverse the paclitaxel-resistance through induction of apoptosis by increasing cleaved PARP and cleaved caspase-3 expression. Moreover, NEAT1 was associated with Akt/mTOR signalling pathway activation by increasing expression of p-Akt, p-mTOR, Bcl-2 and decreasing expression of Bax. In conclusion, these results demonstrated that NEAT1 underlay paclitaxel-resistance in NSCLC.